Türkiye’de Kentsel Koruma Politikalarının Gelişimine Yardımcı Bir Yöntem Denemesi, Örnekleme: İstanbul Tarihi Yarımada - Şahin, İsmet (Fen Bilimleri Enstitüsü, 2015)
Bu çalışmada; Türkiye’de mevcut kavramsal, yasal, kurumsal çerçeve, uygulama araçları ve koruma imar planı süreciyle kültürel ve kentsel mirasın korunmasının mümkün olmadığı ve koruma ile kentsel işlevler arasında olumlu bir ilişki bulunduğu temel kabullerinden hareketle geçerli koruma ilke ve politikaların oluşturulabilmesine yönelik olarak konu sistematik biçimde ele alınmıştır. UNESCO, ICOMOS, Avrupa Konseyi gibi uluslararası kurumların metinleri ile Türkiye’deki yasal çerçeve karşılıklı olarak incelenmiştir. Yanısıra örnekleme alanı olarak seçilen İstanbul’la benzer kriterlere sahip 5 adet yurtiçi ve yurtdışı büyükşehir ile İstanbul Büyükşehir yönetimine özgün anket soruşturmaları uygulanmıştır. Yurtiçi büyükşehir yönetimlerinin koruma imar planları ile İstanbul’un Metropoliten Alan Nazım Planları ve Tarihi Yarımada’nın nazım planlarının tamamı tarihi süreç içerisinde korumaya ilişkin çerçevede incelenerek değerlendirilmiştir. Tarihi Yarımada’ya ilişkin ayrı ve özgün bir anket soruşturması hazırlanarak kriterleri belirlenmiş kurum ve kişilere uygulanmıştır. Yasal metinlerin incelenmesi, alansal analizler ve 3 farklı sistematikle hazırlanan özgün anket soruşturmaları tezde uygulanan deneysel yöntem uygulama araçlarıdır. Yapılan inceleme, analiz ve araştırma sonucu Türkiye’de kentsel ve kültürel mirası korumaya ilişkin kavramsal, yasal, kurumsal çerçeve, planlama süreci ve uygulama araçlarının yeterli olmadığı ve yeniden yapılanmanın gerektiği anlaşılmış, uluslararası geçerli bir korumayı sağlayabilecek yeniden yapılanmaya ilişkin yöntemin altlığını oluşturacak ilke ve politikalar geliştirilmiştir. Ayrıca kentsel mirasın sosyo-ekonomik ve kültürel yönden kentle bütünleşmesi, kentsel işlevler içinde güncellik kazanabilmesi, kentsel işlevlere göre her kent için özel içerikli bir saptama ve değerlendirme yapılmasının gerekliliği saptanarak ve bütüncül planlama anlayışının olmadığı koruma imar planı ve imar planı ikileminin korumayı yeterince saptayamadığının anlaşılmasıyla planlama sürecine çözüm olabilecek planlamanın bütününü kapsayan “İşlevsel Koruma Planlaması Süreci Akış Diyagramı” geliştirilmiştir. Anahtar Kelimeler: Koruma, kültürel ve kentsel miras, kentsel işlev, yeniden yapılanma, işlevsel koruma planlaması Bilim Dalı Sayısal Kodu: 601

In this study; it is seen that impossible to protect cultural and urban hertiage with this existing conceptual,legal,institutional frame,practical tools and public protection plan. Urban heritage is the largest part of the cultural heritage and doubtless the common property of mankind. It contains all of the immovable cultural presence surrounding us. Protection of urban heritage for the sake of common interests and responsibility of mankind depends on recognition of some concepts and understandings internationally. Legal frame in Turkey is examined with some international institutions such as UNESCO, ICOMOS and European Council.Also, the practical examples from our country and other countries concerning the urban protection policies are examined. The surveys have been conducted in the cities meeting the given criteria.The situation of the urban protection policies in Turkey and in the world during the historical period until today are addressed, and the legal, institutional, social, cultural, economical and planning dimensions of urban protection policies are sought. The current protection building planning reports of the Greater Municipalities of Antalya, Bursa, Diyarbakir, Kayseri and Konya which meet the given criteria have been studied, and a survey has been conducted in order to discover the policies applying the urban protection of these cities. The foreign examples are those from the cities meeting majority of the criteria according to the survey conducted among the members of METROPOLIS (World Association of the Major Metropolises) that is one of the International Municipality Organisations participated by Greater Municipalities. The survey covered the cities of the old world consisting of Berlin, London, Athens, Moscow and Toronto from the new world. The situation and policies, to protect, of the cultural heritage have been investigated in the stated cities. All legal and approved master plans and those unapproved master plans made in both metropolitan level and the Historical Peninsula level are examined, and the favourable and unfavourable aims, targets, principles, decisions, evaluations and comments concerning the protection policies for urban heritage in the Historical Peninsula are addressed.The surveys have been conducted in the Historical Peninsula to analyse and synthesise the theoretical, institutional, legal, socio-economical, organisational special functions and the problems concerning urban identity, to produce choices and select one of them. The survey has been prepared with a special scope to disclosure all these problems and to determine policies. In the light of the obtained findings, an evaluation has been made to establish an urban protection policy for the Historical Peninsula suitable to the its conditions in accordance with Master Plans made so far and the current Master Plans, the Urban Protection Plan. As a conclusion,It is internationally common that the uniqueness and difference of urban heritage should be protected and respected. Unlike any movable property or an item exhibited in a museum, urban heritage is within society and surrounds it. It is therefore open to social changes and effects. It has close relations with all physical, social and cultural changes in the social structure.
A Method Experiment For The Improment In Politics Of Urban Protection In Turkey Model: Istanbul Historical Peninsula
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2004
Thesis (PhD) -- İstanbul Technical University, Institute of Science and Technology, 2004
Keywords: Koruma; kültürel ve kentsel miras; kentsel işlev; yeniden yapılanma; işlevsel koruma planlaması; Protection; Cultural and Urban heritage; urban functionalism; reconstruction; functionalist protection planning